The Role of Product Knowledge, Religiosity, and Consumer Attitudes in Shaping Consumer Purchase Intention - Radiansyah, Egi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to examine the influence of product knowledge and religiosity on consumer purchase intention, as well as the mediating role of message trust in this relationship. Product knowledge refers to consumers’ understanding of the attributes, benefits, and characteristics of a product, while religiosity reflects individuals’ beliefs and religious practices. Message trust refers to consumers’ subjective evaluation of messages conveyed through advertisements, product reviews, or other marketing communications. Previous studies have shown that product knowledge and religiosity have the potential to influence consumer purchase intention, with message trust acting as a mediator. This research uses a systematic literature review method to collect and synthesize relevant literature. The findings of this study are expected to provide insights to marketers in designing effective marketing strategies and contribute to theoretical understanding of consumer behavior and its influencing factors. This research will fill the existing knowledge gap in the relationship between product knowledge, religiosity, message trust, and consumer purchase intention.